Delivering Counsellor Training to First Nations: Emerging Issues - Hogan, Emmett P.; Barlow, Constance A. (Canadian Counselling and Psychotherapy Association, 2007)
This paper reports on the preliminary findings of a review of the outcomes of counsellor training programs on two First Nations communities in southern Alberta. Two general themes emerged as prevalent, namely, the continuing influence of the past, and the struggle for cultural survival. This study has indicated that significant modifications are required to the curriculum delivered. However, the data challenge the assumption of a deficit in the relevance and quality of counsellor training provided to First Nations students, suggesting cause for optimism and ongoing collaboration in counsellor education and training between post-secondary institutions and First Nations communities. Cet article étudie les conclusions préliminaires d'une étude sur les résultats des programmes de formation de conseillers dans deux communautés autochtones du sud de l'Alberta. Deux thèmes généraux principaux se dégagent : l'influence continue du passé et le combat pour la survie culturelle. Cette étude indique que des modifications substantielles devront être apportées au curriculum proposé. Néanmoins, les données remettent en question la présomption d'une qualité et d'une pertinence insuffisantes de la formation de conseiller offerte aux étudiants autochtones. Ceci est de bon augure pour une collaboration continue entre les institutions du postsecondaire et les communautés autochtones, en ce qui concerne l'éducation et la formation des conseillers.